Monoamniotic twin pregnancy: is there a need for frequent fetal-doppler surveillance? - Abdullah, Suhaiza; Che Yaakob, Che Anuar; Nik Lah, Nik Ahmad Zuky; Awang, Mokhtar (Faculty of Medicine, International Islamic University Malaysia, 2010)
Monoamniotic twin pregnancy is a rare type of twin pregnancy which poses risk of cord entanglement and sudden death of either one or both fetuses. The role of antenatal surveillance by Ultrasound Doppler for umbilical cord and ultrasonic evidence of cord entanglement or knotting may predict the pregnancy outcome but yet unavoidable. The discussion will include antenatal surveillance in this rare type of pregnancy